NMN deamidase delays Wallerian degeneration and rescues axonal defects caused by NMNAT2 deficiency in vivo - Di Stefano, Michele; Loreto, Andrea; Orsomando, Giuseppe; Mori, Valerio; Zamporlini, Federica; Hulse, Richard P.; Webster, Jamie; Donaldson, Lucy F.; Gering, Martin; Raffaelli, Nadia; Coleman, Michael P.; Gilley, Jonathan; et al. (Elsevier (Cell Press), 2017)
Axons require the axonal NAD-synthesizing enzyme NMNAT2 to survive. Injury or genetically-induced depletion of NMNAT2 triggers axonal degeneration or defective axon growth. We have previously proposed that axonal NMNAT2 primarily promotes axon survival by maintaining low levels of its substrate NMN, rather than generating NAD; however, this is still debated. NMN deamidase, a bacterial enzyme, shares NMN-consuming activity with NMNAT2, but not NAD-synthesizing activity, and delays axon degeneration in primary neuronal cultures. Here, we show that NMN deamidase can also delay axon degeneration in zebrafish larvae and in transgenic mice. Like overexpressed NMNATs, NMN deamidase reduces NMN accumulation in injured mouse sciatic nerves and preserves some axons for up to 3 weeks, even when expressed at a low level. Remarkably, NMN deamidase also rescues axonal outgrowth and perinatal lethality in mice lacking NMNAT2 in a dose-dependent manner. These data further support a pro-degenerative effect of accumulating NMN in axons in vivo. The NMN deamidase mouse will be an important tool to further probe the mechanisms underlying Wallerian degeneration and its prevention.